Understanding Perceived Age-Based Judgement as a Precursor to Age-Based Stereotype Threat in Everyday Settings - Lamont, Ruth A.; Swift, Hannah J.; Drury, Lisbeth (Frontiers in Psychology, 2021)
Test conditions eliciting negative stereotypes of ageing among older adults can prompt age-based stereotype threat (ABST), which results in worse performance on cognitive and memory tests. Much of this research explores ABST as a phenomenon that impacts the performance of older adults. Little is known about the experience of ABST beyond performance settings and how it manifests in everyday contexts across different age groups. Gaps also remain in understanding the wider impacts of ABST, such as effects on task motivation and engagement. The current research addresses this by exploring the contexts in which age-based judgement, a theorised precursor to ABST, occurs across a wide age-range of participants. The two studies in this paper present mixed-methods survey data for a total of 282 respondents aged 18-84 years old. Study 1 presents a thematic analysis of open-ended responses to identify the stereotypes and settings that underpin perceived age-based judgement. The settings and stereotypes identified are discussed in relation to which contexts lend themselves to adverse ABST effects. Study 2 then asked respondents to rate the extent they experience threat-based concern within 12 contexts identified from Study 1. Results indicate differences in threat-based concerns between young, middle-aged and older adults for physical activity, driving, using public transport, using technology, in leadership and relating to the Covid-19 pandemic. The studies provide a foundation for future research to investigate: 1) the motivational and behavioural consequences of threat-based concerns for younger adults’ driving and leadership, and in the context of the pandemic; 2) cues to ‘old’ age stereotypes and threat-based concerns among late middle-aged adults within the workplace; 3) the role of broad stereotypes of ‘incompetence’ and being ‘past-it’ on middle-aged and older adults’ engagement with technology and physical activity; and 4) potential ABST effects resulting from stereotypes of older people as a burden and a problem in the context of a national crisis. Overall, this research extends our understanding of ABST by identifying further contexts and age groups that could be impacted by a wider range of ABST effects.